EFFECT OF BENZYL ADENINE AND SALICYLIC ACID ON GROWTH AND TOTAL ALKALOIDS PRODUCTION OF WETHINIA (Withania somnifera L.) In Vitro - & Majeed, Hamood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment  was conducted in the tissue culture laboratory, College of Education For Pure Science, Diyala Uinversity in 2014-2015,to investigate the influences of Benzyl adenine and Salicylic acid on  growth and total alkaloids production for Wethinia plant )Withania somnifera L (.in vitro .Four concentrations of Benzyl Adenine)BA (0.0, 1, 2 and 3 mg.l-1, which were represented with A0  ،A1 ، A2  and A3  were used respectively، and also four concentrations of Salicylic acid (SA( 0, 10, 20, and 30 mg.l-1 which were represented with B0, B1,B2 and B3 respectively, with the interaction between of Benzyl adenine and Salicylic acid,these are concentrations added to culture media(MS) in multiplication stages. Seeds were soaked with gibberellic acid 500 mg.L-1  for 18 h at room temperature.Benzyl adenine at 1 mg.L-1 significantly increased shoots number 4.22, and Chlrophyll content 34.07 SPAD Unit ,there was no significant differences at 2 mg.L-1 in leaves number12.05 ,11.32, fresh and dry weight of vegetative parts 1.42, 1.40g, and 0.134, 0.128 g, also the addition of SA at 10 mg.L-1 led to increased in number of shoots 3.45, number of  leaves 14.05, dry weight of vegetative parts 0.140 g ,and  fresh weight of root system 0.06 g, there was no significant differences at 20 mg.L-1 in Chlrophyll content 33.77, 35.47 SPAD Unit, fresh weight of vegetative parts,1.47,  1.40g, number of roots 18.00,20.10,  and  percentage of rooting 7.89% ,8.51%. Interaction between of Benzyl adenine and Salicylic acid (A1B1) showed a significant superiority in all studed  vegetative  characters, there was no significant differences with (A2B1) in leaves number15.30, 14.80 leaf, fresh  weight of vegetative parts1.61,1.59 g, dry weight of vegetative parts 0.160 ,0.160 g, A0B1 treat ment which rooted and acclimated  gave 0.105 mg.g-1 total alkaloids.Benzyl adenine at  2 mg.l-1  increased total  alkaloids   0.091 mg.g-1, Salicylic acid at 10 mg.l-1 increased total  alkaloids0.091 mg.g-1,also Interaction  of treatments A2B1  and  A1B1  show a  significant superiority of  total  alkaloids 0.101, 0.100 mg.g-1as  compared with A0B0 which gave lowest content 0.029  mg.g-1.